Rayleigh–Taylor instability by segregation in an evaporating multicomponent microdroplet. (25th September 2020) - Li, Yaxing; Diddens, Christian; Segers, Tim; Wijshoff, Herman; Verluis, Michel; Lohse, Detlef
Abstract: Abstract : The evaporation of multicomponent droplets is relevant to various applications but challenging to study due to the complex physicochemical dynamics. Recently, Li etal. ( Phys. Rev. Lett., vol. 120, 2018, 224501) reported evaporation-triggered segregation in 1, 2-hexanediol–water binary droplets. In this present work, we added 0.5 wt % silicone oil to the 1, 2-hexanediol–water binary solution. This minute silicone oil concentration dramatically modifies the evaporation process, as it triggers an early extraction of the 1, 2-hexanediol from the mixture. Surprisingly, we observe that the segregation of 1, 2-hexanediol forms plumes, rising up from the rim of the sessile droplet towards the apex during droplet evaporation. By orientating the droplet upside down, i.e. by studying a pendent droplet, the absence of the plumes indicates that the flow structure is induced by buoyancy, which drives a Rayleigh–Taylor instability (i.e. driven by density differences and gravitational acceleration). From micro particle image velocimetry measurement, we further prove that the segregation of the non-volatile component (1, 2-hexanediol) hinders the evaporation near the contact line, which leads to a suppression of the Marangoni flow in this region. Hence, on long time scales, gravitational effects, rather than Marangoni flows, play the dominant role in the flow structure. We compare the measurement of the evaporation rate with the diffusion model of Popov ( Phys. Rev., vol. 71, 2005, 036313), coupled with Raoult's law and the activity coefficient. This comparison indeed confirms that the silicone-oil-triggered segregation of the non-volatile 1, 2-hexanediol significantly delays the evaporation. With an extended diffusion model, in which the influence of the segregation has been implemented, the evaporation can be well described.